Laser-induced coherent spin change due to spin-orbit coupling - In Cheol Yu; Jung Hyun Oh; Je-Ho Shim; Kab-Jin Kim; Byong-Guk Park; Dong-Hyun Kim; Kyoung-Whan Kim; Hyun-Woo Lee; Kyung-Jin Lee; Fabian Rotermund (npj Spintronics)
Abstract Direct light-spin interactions, induced by spin-orbit coupling (SOC), enable ultrafast spin manipulation through coherent spin excitation, which is universal in magnetic materials due to the ubiquity of SOC. Despite earlier reports, coherent spin excitation has been overlooked, because of the challenges of interpreting magneto-optical Kerr effect (MOKE) signals and the assumption of optical dipole transitions. By combining time-resolved MOKE measurements with density functional theory calculations, we demonstrate that a transient MOKE peak during laser pulse includes coherent spin excitation. We observe a pronounced transient MOKE peak in Co/Pt bilayer and a weaker one in Co single layer across different probe beam wavelengths. Theoretical calculations reveal that the Co/Pt peak includes contributions from both coherent spin excitation and nonlocal transport whereas the Co peak contains the contribution from the coherent spin excitation exclusively, which is governed by anti-crossing physics. Our findings highlight the SOC-mediated coherent spin dynamics, advancing ultrafast spintronic technology.